2021
DOI: 10.1002/nbm.4474
|View full text |Cite
|
Sign up to set email alerts
|

23Na MRI in ischemic stroke: Acquisition time reduction using postprocessing with convolutional neural networks

Abstract: Quantitative 23Na magnetic resonance imaging (MRI) provides tissue sodium concentration (TSC), which is connected to cell viability and vitality. Long acquisition times are one of the most challenging aspects for its clinical establishment. K‐space undersampling is an approach for acquisition time reduction, but generates noise and artifacts. The use of convolutional neural networks (CNNs) is increasing in medical imaging and they are a useful tool for MRI postprocessing. The aim of this study is 23Na MRI acqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…Fixed sparsifying transform operators are frequently employed in sodium MRI, such as wavelets, 30 finite differences, 15,33,37 or the orthogonal DCT 30 . Moreover, it is possible to perform sparse representation of sodium images based on a trained dictionary, 33,34,36,37 or others 33,39 …”
Section: Basic Principles For the Application Of Compressed Sensing T...mentioning
confidence: 99%
See 4 more Smart Citations
“…Fixed sparsifying transform operators are frequently employed in sodium MRI, such as wavelets, 30 finite differences, 15,33,37 or the orthogonal DCT 30 . Moreover, it is possible to perform sparse representation of sodium images based on a trained dictionary, 33,34,36,37 or others 33,39 …”
Section: Basic Principles For the Application Of Compressed Sensing T...mentioning
confidence: 99%
“…Lachner et al pioneered the combination of parallel imaging with CS sodium MRI in a study on female breast imaging using a multichannel phased‐array sodium/hydrogen double‐tuned coil and found that the incorporation of parallel imaging improved CS reconstruction with higher image quality 38 . More recently, Adlung et al provided proof for the first time that convolutional neural networks in the field of deep learning were able to reconstruct 4‐fold undersampled sodium MRI images with loss functions acting as regularizations while maintaining SNR and TSC quantification accuracy for ischemic stroke patients 39 . The majority of the research relating to CS‐based sodium MRI have been conducted at an ultra‐high field strength of 7 T using various forms of 3D radial sampling schemes with undersampling factors (USFs) ranging from 2 to 10.…”
Section: Historical Milestonesmentioning
confidence: 99%
See 3 more Smart Citations